HOW TO INCREASE UNDERSTANDING OF WASTE MANAGEMENT BY MAKING ECO ENZYMES AT SD NEGERI NO. 2 JEUMPET, DARUL IMARAH DISTRIC ACEH BESAR: UPAYA PENINGKATAN PEMAHAMAN PENGELOLAAN SAMPAH MELALUI PEMBUATAN ECOENZYME DI SDN 2 JEUMPETKECAMATAN DARUL IMARAH ACEH BESAR - Elviani; Nurlia Farida; Ruhalena Wilis; Afrina, Nyak Yusfa; Tasliati Djafar; Umar Husein Abdullah; Cut Maila Hanum (PT. ROCE WISDOM ACEH, 2025)
Waste management is a global issue affecting cities worldwide. The increase in population and the intensity of community activities directly contribute to the increasing volume of waste piles. One of the most significant impacts of this problem is evident in the school environment, where waste accumulation is often a challenge that has not been optimally addressed. This problem is caused by the low level of knowledge and skills of school residents in managing waste, especially organic waste. Therefore, educational and practical efforts are needed to process organic waste, one of which is the manufacture of Eco-Enzyme. The purpose of this activity is to improve the understanding and skills of teachers, education personnel, and students of SD Negeri 2 Jeumpet, Darul Imarah District, Aceh Besar Regency, in processing organic waste into Eco-Enzyme products and to foster awareness and motivation of the school community in supporting environmental conservation and improving the quality of public health. The activity was conducted at SDNegeri 2 Jeumpet, Darul Imarah District, Aceh Besar Regency, from September 20 to December 20, 2024. The series of activities included socialisation and training on the production of eco-enzymes. The evaluation results showed that the participants of the activity, namely teachers, education personnel, and students, showed an increase in knowledge and skills in processing organic waste into Eco-Enzyme. The Eco-Enzyme product produced is used as a cleaning fluid for the environment around the school and home, as well as a liquid fertiliser for yard plants. Overall, this community service activity has a positive impact on increasing environmental awareness among school residents and contributes to forming new mindsets and behaviours that are more responsible for managing organic waste